The Drug-Trafficking Economy and Its Dynamics in Latin America - Pontón C., Daniel (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2013)
This article analyzes the behavior of drug-trafficking economy in Latin America during the last twelve years and its influence in the configuration of a new crime scenario in the region. It is argued that with an economic understanding of drug trafficking one can capture the true capacity of infiltration and cooptation, analyze the wide variations in the supply and demand of these products and their impact on current dynamics of criminality in Latin America, and, lastly, de-construct several myths surrounding this economy. This opens the possibility for a new methodological framework for designing policies that seek to adapt state controlling, neutralization, and prevention capacities to the new and changing rationalities of the world economy of drug trafficking.